2021
DOI: 10.1186/s13244-021-01050-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemosiderin deposition evaluation in hemophilic ankle joints: association between US finding and gradient-recalled echo MR imaging sequence

Abstract: Background Repeated bleeding in hemophilic arthropathy (HA) may result in severe degenerative changes and joint destruction. The gradient-recalled echo (GRE) sequence MR is proved to be the best method to detect hemosiderin deposition. However, MR is not widely available in developing countries, including Indonesia. Some studies have proposed ultrasonography (US) as an alternative tool in evaluating hemophilic joint. However, there is still some disagreement on the ability of US to detect hemos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Such hemosiderin deposits can stimulate further synovial hypertrophy and swelling. 7 Several in vitro and in vivo animal studies have shown how blood has a direct effect on cartilage due to the combination of mononuclear cells and red blood cells present in the blood. 8 The development of hemarthrosis induces chondrocyte apoptosis, which alters the cartilage matrix renewal.…”
Section: Hemophilia Overview and Clinical Manifestationsmentioning
confidence: 99%
“…Such hemosiderin deposits can stimulate further synovial hypertrophy and swelling. 7 Several in vitro and in vivo animal studies have shown how blood has a direct effect on cartilage due to the combination of mononuclear cells and red blood cells present in the blood. 8 The development of hemarthrosis induces chondrocyte apoptosis, which alters the cartilage matrix renewal.…”
Section: Hemophilia Overview and Clinical Manifestationsmentioning
confidence: 99%
“…Such hemosiderin deposition can stimulate further synovial hypertrophy and inflammation. 4 The development of hemarthrosis induces chondrocyte apoptosis, 5 which alters cartilage matrix regeneration. Initially expressed by hypertrophic synovium, hypervascularization occurs on the synovial tissue, increasing the risk of further bleeding, and the onset of inflammatory changes.…”
mentioning
confidence: 99%
“…18 In another study that evaluated ankles in 11 boys with haemophilia, Prasetyo et al evaluated only the ability of US to detect hemosiderin deposits within the joint and determined that the association between the US and MRI for detection of hemosiderin deposits was weak. 19 Additional two studies included children as a part of their study group. Sierra Aisa et al included patients with HA between the age of 4-82 years and reported sensitivity, specificity, positive predictive value, and negative predictive value for diagnosing HA within the same interval as presented in our study.…”
mentioning
confidence: 99%